Impact of contaminated household environment on stunting in children aged 12–59 months in Burkina Faso. Issue 4 (16th December 2016) - Fregonese, Federica; Siekmans, Kendra; Kouanda, Seni; Druetz, Thomas; Ly, Antarou; Diabaté, Souleymane; Haddad, Slim
Abstract : Background: Stunting affects 165 million children worldwide, with repercussions on their survival and development. A contaminated environment is likely to contribute to stunting: frequent faecal-oral transmission possibly causes environmental enteropathy, a chronic inflammatory disorder that may contribute to faltering growth in children. This study's objective was to assess the effect of contaminated environment on stunting in Burkina Faso, where stunting prevalence is persistently high. Methods: Panel study of children aged 1–5 years in Kaya. Household socioeconomic characteristics, food needs and sanitary conditions were measured once, and child growth every year (2011–2014). Using multiple correspondence analysis and 12 questions and observations on water, sanitation, hygiene behaviours, yard cleanliness and animal proximity, we constructed a 'contaminated environment' index as a proxy of faecal-oral transmission exposure. Analysis was performed using a generalised structural equation model (SEM), adjusting for repeat observations and hierarchical data. Results: Stunting (<2 SD height-for-age) prevalence was 29% among 3121 children (median (IQR) age 36 (25–48) months). Environment contamination was widespread, particularly in rural and peri-urban areas, and was associated with stunting (prevalence ratio 1.30; p=0.008), controlling for sex, age, survey year, setting, mother's education, father's occupation, household food security and wealth. This association was significant for children of all ages (1–5 years) and settings. Lower contamination and higher food security had effects of comparable magnitude. Conclusions: Environment contamination can be at least as influential as nutritional components in the pathway to stunting. There is a rationale for including interventions to reduce environment contamination in stunting prevention programmes.